Pemberantasan Kanker di Yogyakarta - Soeripto, Soeripto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
Cimpaign against cancer is not only the duty of the medical professional but also the responÃ¢â¬Â¢ sibility of the society. The activities of the Sardjito Teaching Hospital Cancer Team.